Novel nonsense mutation in MSX1 in familial nonsyndromic oligodontia: subcellular localization and role of homeodomain/MH4. (11th December 2013) - Kimura, Masashi; Machida, Junichiro; Yamaguchi, Seishi; Shibata, Akio; Tatematsu, Tadashi; Miyachi, Hitoshi; Jezewski, Peter A.; Nakayama, Atsuo; Higashi, Yujiro; Shimozato, Kazuo; Tokita, Yoshihito
<x xml:space="preserve">Abstract</x> Nonsyndromic tooth agenesis is one of the most common anomalies in human development. Part of the malformation is inherited and is associated with paired box 9 (PAX9), msh homeobox 1 (MSX1), and axin 2 (AXIN2) mutations. To obtain a comprehensive understanding of the genetic and molecular mechanisms that underlie this genetic disease, we investigated six familial and seven sporadic Japanese cases of nonsyndromic tooth agenesis. Searches for mutations in these candidate genes detected a novel nonsense mutation (c.416G>A) in exon 1 of MSX1 from a family with oligodontia. This mutation co‐segregated in the affected family members. Moreover, this mutation produced a termination codon in the first exon and therefore the gene product (W139X) was truncated at the C terminus, hence, the entire homeodomain/MH4, which has many functions, such as DNA binding, protein‐protein interaction, and nuclear localization, was absent. We characterized the properties of this truncated MSX1 by investigating the subcellular localization of the mutant gene product in transfected cells. The wild‐type MSX1 localized exclusively at the nuclear periphery of transfected cells, whereas the mutant MSX1 was stable but localized diffusely throughout the whole cell. These results indicate that W139X MSX1 is responsible for tooth agenesis.